Dig your well before you're thirsty the only networking book you'll ever need - Mackay, Harvey (Currency, 1997)
Harvey Mackay, who taught millions of Americans how to "swim with the sharks without getting eaten alive" now dives deep into the art of which he's grandmaster: networking. Dig Your Well Before You're Thirsty contains Harvey's gold-chip advice, accumulated over a lifetime of business success, on how to build and maintain the network you need. Harvey guarantees you'll never be more than a phone call away from a person in the position to help you get what you want
Keywords: Business networks; Social networks; Zwischenmenschliche Beziehung; Ratgeber